2017
DOI: 10.1186/s12960-017-0205-4
|View full text |Cite
|
Sign up to set email alerts
|

Health workforce and governance: the crisis in Nigeria

Abstract: BackgroundIn Nigeria, several challenges have been reported within the health sector, especially in training, funding, employment, and deployment of the health workforce. We aimed to review recent health workforce crises in the Nigerian health sector to identify key underlying causes and provide recommendations toward preventing and/or managing potential future crises in Nigeria.MethodsWe conducted a scoping literature search of PubMed to identify studies on health workforce and health governance in Nigeria. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 19 publications
(31 reference statements)
5
137
1
Order By: Relevance
“…The moderate level of distributive justice might be due to perception by all health professionals that salaries, promotional opportunities and hospital resources are generally insufficient. Inadequate pay and hospital resources have been reasons for industrial actions in Nigeria [13,[15][16][17]28]. However, our findings that nurses and AHPs had significantly lower perception of distributive justice than doctors validate findings of a previous Nigerian study [11].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The moderate level of distributive justice might be due to perception by all health professionals that salaries, promotional opportunities and hospital resources are generally insufficient. Inadequate pay and hospital resources have been reasons for industrial actions in Nigeria [13,[15][16][17]28]. However, our findings that nurses and AHPs had significantly lower perception of distributive justice than doctors validate findings of a previous Nigerian study [11].…”
Section: Discussionsupporting
confidence: 84%
“…In Nigeria, evidence of organizational injustice, deriving from studies on industrial actions, inter-professional conflict, and health workforce governance highlight the huge organizational challenges in managing and motivating healthcare professionals for effective performance in Nigeria especially importance of rewards, professional dominance and work climate [13,[15][16][17]28]. Although there are growing concerns about whether rewards and hospital resources are allocated to healthcare professionals equitably and whether such allocation decisions are made according to fair methods and guidelines, studies on perceptions of organizational justice among health workers in Nigeria are scarce [11].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Effective clinical leadership is closely associated with a wide range of hospital functions, and it forms an integral component of the health care system. Unfortunately, poor administration and leadership has been persistently bedevilling the Nigerian health care system for many years, and it is the root cause of numerous industrial actions and unrest [14]. Developing clinical leadership skills among ECDs and other health professionals is of critical importance in changing the current trend.…”
Section: Discussionmentioning
confidence: 99%
“…African Development Bank Report (2016) indicates that young people continues to be a powerful work force for development. Additionally, Adeloye et al (2017) reported that shortage of human resources for health has been the main barrier to scale-up health systems and health specific interventions. Previous studies have shown direct links between efficient health system governance and promising health workers outputs, which ultimately have positive effects on overall health outcomes (Adeloye et al, 2017).…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%